Chapter 6 Conflict Management Redux Desecuritizing Intractable Conflicts - Vuković, Siniša (Taylor & Francis, 2019)
This book seeks to interrogate how contemporary policy issues become 'securitized' and, furthermore, what the implications of this process are. A generation after the introduction of the concept of securitization to the security studies field, this book engages with how securitization and desecuritization 'works' within and across a wide range of security domains including terrorism and counter-terrorism, climate change, sexual and gender-based violence, inter-state and intra-state conflict, identity, and memory in various geographic and social contexts. Blending theory and application, the contributors to this volume - drawn from different disciplinary, ontological, and geographic 'spaces' - orient their investigations around three common analytical objectives: revealing deficiencies in and through application(s) of securitization; considering securitization through speech-acts and discourse as well as other mechanisms; and exposing latent orthodoxies embedded in securitization research. The volume demonstrates the dynamic and elastic quality of securitization and desecuritization as concepts that bear explanatory fruit when applied across a wide range of security issues, actors, and audiences. It also reveals the deficiencies in restricting securitization research to an overly narrow set of issues, actors, and mechanisms. This volume will be of great interest to scholars of critical security studies, international security, and International Relations.